HIV/AIDS-related Expectations and Risky Sexual Behaviour in Malawi - Delavande, Adeline; Kohler, Hans-Peter (Review of Economic Studies, 2016)
We use probabilistic expectations data elicited from survey respondents in rural Malawi to investigate how risky sexual behaviour may be influenced by individuals' expectations about survival, and future HIV status, which in turn depend on the perceived impact of HIV/AIDS on survival, expectations about own and partner's current HIV status, and expectations about HIV transmission rates. Subjective expectations, in particular about mortality risk but not the risk of living with HIV, play an important role in determining the decision to have multiple sexual partners. Using our estimated parameters, we simulate the impact of various policies that would influence expectations. An information campaign on mortality risk would decrease risky sexual behaviour on average, whereas an information campaign on HIV transmission risks, which tend to be overestimated by respondents, would actually increase risky behaviour. Also, the expansion of anti-retroviral therapy (ART) treatments to all individuals infected with HIV would increase risky sexual behaviour for a quarter of the HIV-negative individuals or those who have not been tested because they are aware that ART increases life expectancy, and thus reduces the cost of becoming HIV positive.